2016
DOI: 10.1016/j.puhe.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the frequency of physical activity very brief advice for cancer patients. Development of an intervention using the behaviour change wheel

Abstract: The BCW is a time consuming process, however, it provides a useful and comprehensive framework for intervention development and greater control over intervention replication and evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 39 publications
0
65
0
Order By: Relevance
“…The online training was developed by Webb, Foster and Poulter (2016) 2 to overcome an identified knowledge gap in nurses regarding the importance of physical activity for cancer patients. 3 Healthcare professionals are expected to give lifestyle advice 4 yet in a UK survey of 15,524 colorectal cancer patients, only 31% recall receiving such advice.…”
Section: The Online Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…The online training was developed by Webb, Foster and Poulter (2016) 2 to overcome an identified knowledge gap in nurses regarding the importance of physical activity for cancer patients. 3 Healthcare professionals are expected to give lifestyle advice 4 yet in a UK survey of 15,524 colorectal cancer patients, only 31% recall receiving such advice.…”
Section: The Online Trainingmentioning
confidence: 99%
“…Details of training development and feasibility have been reported previously. 2,7 The original training was designed specifically for nurses however, a recommendation from the feasibility study was that it be open to all healthcare professionals engaging with cancer patients. 2 Online seminar technology is used to deliver the training, providing a virtual medium for peer-to-peer interaction, important for learner engagement and social learning.…”
Section: The Online Trainingmentioning
confidence: 99%
“…[1][2][3][4][5]11 Despite the exercise recommendations noted above, an analysis of greater than 9000 cancer survivors from the ACS Study of Cancer Survivors II (SCS-II) cohort indicated that only between 30% and 47% met current physical activity guidelines. 12,13 In the Health Information National Trends Survey (HINTS) cohort, approximately 45% of cancer survivors reported regular physical activity, although this varied by tumor site (32% vs 53% in breast cancer vs prostate cancer survivors, respectively). 9 Data from the United Kingdom indicated that 31% of people living with and beyond cancer are completely inactive.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Despite this, studies suggest that 9% of nurses and from 19% to 23% of oncology physicians refer patients with cancer to exercise programming. 13,17,21,22 A recent survey of 971 oncology clinicians that was conducted by the American Society of Clinical Oncology indicated that 78.9% of respondents agreed that oncology clinicians should recommend physical activity to their patients. 23 Observed barriers to clinicians referring patients to exercise programming include lack of awareness of the potential value of exercise in cancer populations, uncertainty regarding the safety or suitability of exercise for a particular patient, lack of awareness regarding available programs to help facilitate exercise in cancer populations, need for education and skills development for making referrals, and a belief that referrals to exercise programming are not within the scope of practice for oncology clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…The BCW has been applied to understand behavioural determinants and design interventions aimed at instilling good hygiene habits in schools in Uganda [14], development of caregiver hygiene behaviour measures [15] and other health related interventions [16][17][18][19][20][21][22]. The approach involves three stages: (1) Understanding the behaviour and identifying what needs to change (2) Identifying Intervention Functions (3) Identifying content and relevant 'Delivery mode' for the intervention.…”
Section: Theoretical Approachmentioning
confidence: 99%